Gadolinium silicide (Gd5Si4) nanoparticles for tuneable broad band microwave absorption. (27th February 2019) - Bora, Pritom J; Harstad, S M; Gupta, S; Pecharsky, V K; Vinoy, K J; Ramamurthy, Praveen C; Hadimani, R L
Abstract: Soft magnetic Gd5 Si4 nanoparticles exhibit excellent microwave absorption in the Ku-band (12.4-18 GHz) when dispersed in poly (dimethyl siloxane), PDMS. The minimum experimentally recorded reflection loss (RL) of Gd5 Si4 -PDMS nanocomposite is −69 dB, with a large bandwidth for a single 6 mm-thick layer. The bandwidth can be further extended by using a novel design where 1 mm-thick layers of the nanocomposite are arranged into a modified pyramid-shaped absorber. Standard electromagnetic (EM) simulations confirm experimental results.